A sandwich-type POM containing mixed cations: synthesis, thermal performance and proton-conducting properties. Issue 3 (1st February 2016) - Li, Shujun; Zhang, Fanyu; Peng, Qingpo; Chen, Xuenian; Wang, Ruoya; Wang, Zhifang; Ma, Fengji; Zhao, Qianyi; Wei, Meilin
Abstract: A new sandwich-type polyoxometalate, Na5 H[N(CH3 )4 ]2 [Co(C3 N2 H4 )2 (H2 O)4 ][Co4 (H2 O)2 (PW9 O34 )2 ]·21H2 O (1 ), has been synthesized.1 is composed of a Weakley-type polyanion, [Co4( H2 O)2 (PW9 O34 )2 ] 10−, four kinds of cations (five Na +, two [N(CH3 )4 ] +, one [Co(C3 N2 H4 )2 (H2 O)4 ] 2+, and one H + ), and 21 crystalline H2 O molecules. The surface oxygen of the polyanion in1, the crystalline water, and coordinated water molecules make an extended 3-D hydrogen-bonding network. Alternating current (AC) impedance experiments of1 reveal good proton conductivity for1 of 5.03 × 10 − 4 S cm −1 at 25 °C under 98% relative humidity (RH). Activation energy of1 calculated from Arrhenius plots is 0.358 eV, indicating Grotthuss mechanism is dominant in the proton transfer. Thermal decomposition behavior of1 was examined by thermogravimetry/mass spectrometry (TG/MS) measurements. Abstract :